Income Tax Competition at the State and Local Level in Switzerland - Lars P. Feld; Gebhard Kirchgässner (Center for Economic Studies and ifo Institute (CESifo), 2000)
Tax competition is supposed to lead to inefficiencies in the provision of public goods and difficulties for decentralized redistribution. A necessary condition for these ef fects to occur is that residence and location decisions are determined by fiscal considerations. In this paper, the impact of personal income taxes and transfer payments on residence decisions of taxpayers is analyzed using cross sectional data on the dis tribution of different groups of taxpayers in different income groups among the 26 Swiss cantons and the 137 largest Swiss cities. We find that tax competition with respect to personal income taxes is relatively strong in Switzerland.
Keywords: 330; Tax competition; fiscal federalism; personal income taxes; transfer payments